Effects of air abrasion with alumina or glass beads on surface characteristics of CAD/CAM composite materials and the bond strength of resin cements - ARAO Nobuaki; YOSHIDA Keiichi; SAWASE Takashi (University of São Paulo, 2015)
ABSTRACT Objective The study aimed to evaluate effects of air abrasion with alumina or glass beads on bond strengths of resin cements to CAD/CAM composite materials. Material and Methods CAD/CAM composite block materials [Cerasmart (CS) and Block HC (BHC)] were pretreated as follows: (a) no treatment (None), (b) application of a ceramic primer (CP), (c) alumina-blasting at 0.2 MPa (AB), (d) AB followed by CP (AB+CP), and (e) glass-beads blasting at 0.4 MPa (GBB) followed by CP (GBB+CP). The composite specimens were bonded to resin composite disks using resin cements [G-CEM Cerasmart (GCCS) and ResiCem (RC)]. The bond strengths after 24 h (TC 0) and after thermal cycling (TC 10,000 at 4-60°C) were measured by shear tests. Three-way ANOVA and the Tukey compromise post hoc tests were used to analyze statistically significant differences between groups (α=0.05). Results For both CAD/CAM composite materials, the None group exhibited a significant decrease in bond strength after TC 10,000 (p<0.05). AB showed significantly higher bond strength after TC 10,000 than the None group, while CP did not (p<0.05). GBB exhibited smaller surface defects than did AB; however, their surface roughnesses were not significantly different (p>0.05). The AB+CP group showed a significantly higher bond strength after TC 10,000 than did the AB group for RC (p<0.05), but not for GCCS. The GBB+CP group showed the highest bond strength for both thermal cyclings (p<0.05). Conclusions Air abrasion with glass beads was more effective in increasing bond durability between the resin cements and CAD/CAM composite materials than was using an alumina powder and a CP.